Implementing ISO-Based Educational Reform: ISO 21001:2018 Effectiveness in Enhancing State Islamic University Services - Alifana, Fairus Tahta; Fauzi, Imron; Lama, Alma Vorfi (JURNAL AL-TANZIM, 2025)
Ensuring high-quality educational services is a growing challenge for State Islamic Universities (UIN) in Indonesia, particularly in efforts to harmonise Islamic educational values with international standards. This study aims to assess the effectiveness of ISO 21001:2018 implementation in improving service quality at State Islamic Religious Universities. The method used is a qualitative case study, with data collection through in-depth interviews, participant observation, and document analysis. Data were obtained from 25 purposively selected informants, consisting of quality assurance staff, lecturers, and students. The results show that ISO 21001:2018 significantly improves institutional accreditation through standardising quality management processes and strengthening human resources and infrastructure. The certification process increases stakeholder trust and strengthens academic quality assurance through regular evaluations and transparent audits. The integration of ISO 21001:2018 also encourages the creation of a participatory environment and continuous improvement in educational services. This study emphasises the importance of adapting international standards to local educational contexts and religious values. The ISO 21001:2018 structure can be a strategic model for quality governance in other Islamic universities.